Optimization of the Center for UMKM Madura Creative Industry: Business and Environmental Feasibility Approach - Ahmad Kamil (MediaTrend, 2022)
The establishment of the SME centers by the Bangkalan District Government, as a tool and effort of the Government to overcome obstacles due to the size of SMEs. Through the SME centers that are formed, it is expected to be able to successfully overcome competition in an increasingly competitive market environment. Referring to the description above, it is deemed necessary to conduct a study of the Center for Leading SMEs in Madura Island with the Business Feasibility Analysis Approach, as a material for taking policy regarding the development of SMEs in Madura Island.70 percent of the NPV value in the cracker business center is positive, which means the value of the NPV produced is greater than zero and falls into the feasible criteria. Likewise, the B / C Ratio produced as much as 60 percent is known to be positive, this positive value means that the calculation results are known to be more than 1 so that they are declared feasible. Thus it can be concluded that the SME centers are declared viable. Whereas the IRR value is a method for calculating the interest rate that can equalize the present value of all net cash flows with cash outflows from an investment.In the environmental aspect, UMKM does not produce waste that can pollute the soil, water, air or sound. If examined further there will be waste oil which if not managed properly will harm the environment and surrounding communities. But until now it can be handled so as to minimize the impact of the waste